Proton beam therapy reirradiation for breast cancer: Multi‐institutional prospective PCG registry analysis. Issue 6 (23rd July 2019) - Thorpe, Cameron S.; Niska, Joshua R.; Girardo, Marlene E.; Kosiorek, Heidi E.; McGee, Lisa A.; Hartsell, William F.; Larson, Gary L.; Tsai, Henry K.; Rossi, Carl J.; Rosen, Lane R.; Vargas, Carlos E.
Abstract: To investigate adverse events (AEs, CTCAE v4.0) and clinical outcomes for proton beam therapy (PBT) reirradiation (reRT) for breast cancer. From 2011 to 2016, 50 patients received PBT reRT for breast cancer in the prospective Proton Collaborative Group (PCG) registry. Acute AEs occurred within 180 days from start of reRT. Late AEs began or persisted beyond 180 days. Fisher's exact and Mann‐Whitney rank‐sum tests were utilized. Kaplan‐Meier methods were used to estimate overall survival (OS) and local recurrence‐free survival (LFRS). Median follow‐up was 12.7 months (0‐41.8). Median prior RT dose was 60 Gy (10‐96.7). Median reRT dose was 55.1 Gy (45.1‐76.3). Median cumulative dose was 110.6 Gy (70.6‐156.8). Median interval between RT courses was 103.8 months (5.5‐430.8). ReRT included regional nodes in 84% (66% internal mammary node [IMN]). Surgery included the following: 44% mastectomy, 22% wide local excision, 6% lumpectomy, 2% reduction mammoplasty, and 26% no surgery. Grade 3 AEs were experienced by 16% of patients (10% acute, 8% late) and were associated with body mass index (BMI) > 30 kg/m 2 ( P  = 0.04), bilateral recurrence ( P  = 0.02), and bilateral reRT ( P  = 0.004). All grade 3 AEs occurred in patients receiving IMN reRT ( P  = 0.08). At 1 year, LRFS was 93%, and OS was 97%. Patients with gross disease at time of PBT trended toward worse 1‐year LRFS (100% without vs. 84% with, P  = 0.06). PBT reRT is well tolerated with favorable local control. BMI > 30, bilateral disease, and IMN reRT were associated with grade 3 AEs. Toxicity was acceptable despite median cumulative dose > 110 Gy.